7(x+3=-49

Simple and best practice solution for 7(x+3=-49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+3=-49 equation:



7(x+3=-49
We move all terms to the left:
7(x+3-(-49)=0

See similar equations:

| -18=2+3(d+7) | | -2(2k-4)=24 | | 16−5a+2a−1=41−a | | 4x-10/5=2x+8 | | 3=1/5+x | | (5x-5)=(7x+1) | | -5-3x=56-28x | | -45=5/3+5b | | 2+3x=-2(6-2x) | | 2(3-h)6=-5h | | -2(14-6x)=20 | | x∧2=4 | | 4x+8=2x+15–x+2 | | 7=1.50x | | 0.12x=420 | | 6a+3=16 | | (x-17)(7x+5)=0 | | -24=−24=-3w+21−3w+21 | | 4x•9=37 | | 8x-1=7x-9 | | -5+n/7=-7 | | 2(n+3)+4(n+2)=74 | | 108+2x+6=13x-7 | | m^2=0.64 | | 15x=6.25x+1890 | | 8(x+4)-3=2x+6(4+x) | | -12=3k-6 | | 6p-3=8-4p | | b3-4=3 | | a+2.8=1.9 | | 2d-½=5/4 | | 17=-0.5p |

Equations solver categories